ALTERNATIVE NATURAL SWEETENERS AS SUGAR SUBSTITUTES USED IN MAKING ICE CREAM - MARIANA VIOLETA POPESCU; ADRIANA DABIJA; ANCUȚA CHETRARIU (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Ice cream is a frozen dessert highly appreciated by all categories of consumers. Lately, consumers' attention is focused on healthy products, with as few ingredients as possible or with natural ingredients. By definition, ice cream is a sweet product. As a rule, sugar is used to obtain ice cream for its characteristics (sweet taste, creaminess, texture, melting time), but the new requirements require the addition or substitution of sugar with other sweeteners. Consumers still prefer the sweet taste of artificial sweeteners, but they are cultivating their taste and increasingly choosing natural nutritious or non-nutritive sweeteners as consumer awareness of healthy foods has increased. This manuscript was based on the study of the literature regarding the use of natural sweeteners in ice cream formulations.